EVALUASI PENERIMAAN PAJAK USAHA MIKRO KECIL DAN MENENGAH (UMKM) PASCA PENERBITAN PERATURAN PEMERINTAH NOMOR 23 TAHUN 2018 DI KOTA TOMOHON - Siallagan, Bernita; Ilat, Ventje; Runtu, Treesje (Universitas Sam Ratulangi, 2020)
Micro, Small and Medium Enterprises are business sectors that have large tax revenue opportunities. The development of Micro, Small and Medium Enterprises (MSMEs) contributes positively to the handling of economic and social problems. Micro, Small and Medium Enterprises (MSMEs) can help the government in reducing poverty, reducing the amount of unemployment, and social inequality. In helping to increase this small and medium economic activity, the government provides tax services for MSME taxpayers with a 0.5% tax rate on gross income not exceeding Rp4.8 Billion. PP No. 23 of 2018 concerning the imposition of MSME tax. This study aims to evaluate how the level of UMKM tax revenue when PP No. 46 of 2013 and when the PP No. 23 of 2018. The method used in this study is a comparative descriptive analysis method. The results showed that the growth of taxpayers who make payments increased while UMKM tax revenues decreased due to tariff cuts